2011
DOI: 10.1002/jnr.22556
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia prevents nitric oxide system changes in retina induced by severe perinatal asphyxia

Abstract: BACKGROUND. Health‐related quality of life (HRQOL) has not been adequately measured in bladder cancer. A recently developed reliable and disease‐specific quality of life instrument (Bladder Cancer Index, BCI) was used to measure urinary, sexual, and bowel function and bother domains in patients with bladder cancer managed with several different interventions, including cystectomy and endoscopic‐based procedures. METHODS. Patients with bladder cancer were identified from a prospective bladder cancer outcomes da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 77 publications
(133 reference statements)
1
27
0
7
Order By: Relevance
“…Therefore MB could be useful in reducing IPR development. Previously, we showed that NO increases in the retina 21 days after injury (45). Here we determined that application of MB inhibited NOS enzymatic activity, thus blocking the NO-dependent neurotoxic cascade.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Therefore MB could be useful in reducing IPR development. Previously, we showed that NO increases in the retina 21 days after injury (45). Here we determined that application of MB inhibited NOS enzymatic activity, thus blocking the NO-dependent neurotoxic cascade.…”
Section: Discussionmentioning
confidence: 71%
“…In this region, we identified enhanced expression of nNOS in amacrine and ganglion cells following experimental asphyxia (45). Excessive production of NO could be highly toxic, combining with other reactive oxygen species to form peroxynitrite and destroying vital cell components (47).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations